Persistent Left Superior Vena Cava Suggested by an Unusual Central Venous Pressure Waveform - Dontukurthy, Sujana; Yamaguchi, Yoshikazu; Tobias, Joseph D. (The Thoracic and Cardiovascular Surgeon Reports, 2020)
Background A persistent left superior vena cava (PLSVC) is the most common congenital anomaly of the thoracic venous return.Case Description During atrial septal defect repair, a pulmonary artery (PA) catheter was placed via the left internal jugular vein. Although placement of the PA catheter in the main PA was confirmed by transesophageal echocardiography, the central venous pressure (CVP) waveform was abnormal. Intraoperatively, the PA catheter was seen exiting the coronary sinus with the CVP port within the coronary sinus.Conclusions The diagnosis of PLSVC is discussed and the differential diagnosis of the abnormal “ventricular” pattern of the CVP waveform is reviewed.
Keywords: cardiovascular surgery; myocardial protection; anatomy; congenital heart disease; CHD